Pelatihan Berbasis Praktik dalam Pengembangan Produk Handmade untuk Meningkatkan Creative Entrepreneurship Mahasiswa - Vera Siwi Astuti; Anggit Dyah Kusumastuti (LPPPM STAI Darul Hikmah Bangkalan, 2026)
This community service program aimed to enhance students’ creativity and creative entrepreneurship through hands-on training in developing handmade phone holders using pipe cleaners. The program involved 17 Business Administration students at Universitas Sahid Surakarta and applied an experiential learning approach consisting of lectures, demonstrations, practice sessions, mentoring, and product evaluation. The results showed improvements in participants’ creativity, particularly in originality, design flexibility, functionality, aesthetics, and innovation. In addition, 82% of participants achieved good to very good levels of entrepreneurial understanding. The training effectively improved students’ technical skills, creativity, and entrepreneurial awareness through direct learning experiences